Leagility in the healthcare research: a systematic review - Xueying Li; Ana Lúcia Martins (BMC, 2024)
Abstract Background Expenditure of healthcare services has been growing over the past decades. Lean and agile are two popular paradigms that could potentially contain cost and improve proficiency of the healthcare system. However no systematic review was found on leagilty in the healthcare research. This study aims at synthesizing the extant literature of leagility in the healthcare area to consolidate its potential and identify research gaps for future study in the field. Methods A systematic literature review is conducted following the PRISMA checklist approach. Studies were searched in multiple databases. The selection of articles was executed by dual-scanning of two researchers to ensure quality of data and relevance to the topic. Scientific articles published between January 1999 and November 2023 concerning leagile healthcare are analysed using Microsoft Excel and VOSviewer (version 1.6.18). Results Out of 270 articles identified from the inclusion and exclusion criteria, 24 were included in the review. A total of 11 target areas were identified in leagility applications in healthcare. Success and limiting factors of leagile healthcare were classified into macro and micro aspects and further categorized into six dimensions: policy, organization, human resources, marketing, operation management and technology. Moreover, four research gaps were revealed and suggestions were provided for future study. Conclusion Leagility in the healthcare context is still being in its infancy. Few empirical validation was found in leagile healthcare literature. Further exploration into the application of theory in various sectors under the scope of healthcare is appealed for. Standardization and modularization, leadership support, skillfulness of professionals and staff training are the factors most frequently mentioned for a successful implementation of leagility in the healthcare sector.